Robert Bresson's Au hasard Balthazar - Schubert, Franz 1797-1828; Wiéner, Jean 1896-1982 (The Criterion Coll., 2005)
Robert Bresson's masterpiece follows a much-abused donkey, Balthazar, whose life strangely parallels that of his owner, Marie. A beast of burden suffering the sins of man, Balthazar nevertheless nobly accepts his fate.
Aspect ratio 1.66:1, 16:9 widescreen. - New, restored high-definition digital transfer
Orig.: Frankreich, Schweden 1966
Enth. new video interview with film scholar Donald Richie (14 min.) ; "Un metteur en ordre: Robert Bresson", a 1966 French television show about the film, featuring Bresson, Jean-Luc Godard, Louis Malle, and members of "Balthazar's" cast and crew ; Original theatrical trailer. Plus: a new essay by film scholar James Quandt
Keywords: Animal welfare -- Drama; Donkeys -- Drama; Feature films; Human-animal relationships -- Drama; French films